The effect of NaOCl and heat treatment on static and dynamic mechanical properties and chemical changes of dentine. (September 2019) - Karunanayake, G.; Ng, Y.-L.; Knowles, J.C.; Delgado, A.H.S.; Young, A.M.; Gulabivala, K.; Nazhat, S.N.
Abstract: Objectives: To determine the effect of heat on flexural strength (FS), maximum strain (MS), storage modulus (SM), tan delta (TD) and chemical changes through micro-Raman spectroscopy of dentine exposed to 2.5% NaOCl or saline. Method: ology: Dentine bars were randomly allocated to 8 test groups. Half (groups 2, 4, 6, 8) were treated with NaOCl for 20 min; the rest (groups 1, 3, 5, 7) remained in saline. FS/MS were measured in groups 1–4 (n = 15) (3/4 were also heated to 200 °C & re-hydrated in saline). Micro-Raman spectroscopy was performed on bars from groups 1–4. SM/TD were measured in 5–8: in 5/6 (n = 10), repeated after heating (200 °C), then following re-hydration; in 7/8 (n = 3) after heating to 25–185 °C. Results: Increase in MS on heat and FS/MS on heat + NaOCl was not significant (P > 0.05). SM increased (P = 0.06) after heat treatment but reduced to initial state after rehydration (P = 0.03). TD did not change (P = 0.4) after heat (200 °C) treatment but rehydration increased it compared with pre-treatment state (P = 0.001). For dentine bars pre-treated with NaOCl, SM did not change (P = 0.6) after heat (200 °C) treatment or rehydration but TD significantly increased (P = 0.02) upon re-hydration compared with pre- (P = 0.007), or post- (P = 0.03) heat-treatment states. SM and TD varied between 25–185 °C with no consistent trend amongst the NaOCl pre-treated bars. Micro-Raman only detected chemical changes following NaOCl treatment in the mineral phase. Conclusions: Exposure of dentine bars to heat and NaOCl produced only moderate changes to quasi-static but marked changes to viscoelastic properties, which may be explained by chemical alterations. Highlights: Exposure of dentine to heat and NaOCl produced moderate changes to quasi-static properties. Exposure of dentine to heat and NaOCl produced marked changes to viscoelastic properties. Heat depleted dentine hydroxyapatite exposed to saline but increased it with NaOCl; together they acted interactively. NaOCl treatment resulted in an increase in carbonate peak in the Raman spectra.